2016
DOI: 10.18632/oncotarget.9053
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a panel of high-grade serous ovarian cancer cell lines as representative experimental models of the disease

Abstract: Genomic analysis of ovarian cancer cell lines has revealed a panel that best represents the most common ovarian cancer subtype, high-grade serous ovarian cancer (HGSOC). However, these HGSOC-like cell lines have not been extensively applied by ovarian cancer researchers to date, and the most commonly used cell lines in the ovarian cancer field do not genetically resemble the major clinical type of the disease. For the HGSOC-like lines to serve as suitable models, they need to be characterized for common functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 25 publications
5
74
1
Order By: Relevance
“…To determine whether EGLN1 dependency was enriched in a specific subtype, we grouped the ovarian cancer cell lines by historical pathologic, molecular, and histologic subtypes ( Supplementary Table S5; adapted from refs. 31,34,36). We found that EGLN1 dependency was significantly enriched in ovarian clear cell carcinoma lines compared with every other ovarian subtype ( Fig.…”
Section: Egln1 Dependency Is Enriched In Ovarian Clear Cell Carcinomamentioning
confidence: 71%
See 1 more Smart Citation
“…To determine whether EGLN1 dependency was enriched in a specific subtype, we grouped the ovarian cancer cell lines by historical pathologic, molecular, and histologic subtypes ( Supplementary Table S5; adapted from refs. 31,34,36). We found that EGLN1 dependency was significantly enriched in ovarian clear cell carcinoma lines compared with every other ovarian subtype ( Fig.…”
Section: Egln1 Dependency Is Enriched In Ovarian Clear Cell Carcinomamentioning
confidence: 71%
“…S2C). Ovarian cancer represents a heterogeneous disease comprised of four major different subtypes (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). To determine whether EGLN1 dependency was enriched in a specific subtype, we grouped the ovarian cancer cell lines by historical pathologic, molecular, and histologic subtypes ( Supplementary Table S5; adapted from refs.…”
Section: Egln1 Dependency Is Enriched In Ovarian Clear Cell Carcinomamentioning
confidence: 99%
“…Shultz and coworkers recently identified a subset of OC cells that — in contrast to lines often employed — more closely resembles the copy‐number changes, mutations, and mRNA expression profiles presented by high‐grade serous ovarian tumors. We and others later identified cell lines among these whose phenotypic and histopathological features, in vivo, further aligned with that of the human disease. In these studies, we selected the OVCAR8 cell line due to its relatively aggressive growth rate, strongly mesenchymal phenotype, ability to form intraperitoneal tumors with high‐grade histopathological features, and murine disease accompaniment by ascitic fluid accumulation.…”
Section: Resultsmentioning
confidence: 80%
“…Chemotherapeutic drugs, cumulative stoichiometric ratios, and excipients employed here were consistent with current National Comprehensive Cancer Network (NCCN) treatment guidelines for intraperitoneal OC chemotherapy (stages II–IV). A relatively modest dose of cisplatin was used in this case as OVCAR8 is a platinum‐sensitive cell line.…”
Section: Resultsmentioning
confidence: 99%
“…MEK1/2-ERK1/2 signaling inhibition in ovarian cancer cells is reported to sensitize them to chemotherapy [47], so MEK1/2 pathway hyperactivation could be a mechanism allowing HGSOC cells to overcome cytotoxic effects of cisplatin. Cisplatin-induced MEK1/2 activation in OVCAR8 and PEO4 cell lines established from recurrent tumors, which already obtained cisplatin resistance [52][53][54], suggests that repeated cisplatin treatment can further promote MEK1/2-ERK1/2 activity and associated chemoresistance in HGSOC.…”
Section: Discussionmentioning
confidence: 99%